TAFSIR KHAWARIJ DALAM PERSFEKTIF PERPOLITIKAN ISLAM - Bustami Saladin (UIN Mataram, 2018)
Khawarij is part of the followers of Ali ibn Abi Talib who then revolted to Ali, at the same time this group was born and born also of opinion and their interpretation of the verses of the Qur'an. Kharijites have started their periods at a glorious reign of the Umayyad Daula, their interpretation of some Qur'anic verses are very frontal, they interpret the verses of the Qur'an without contemplation of a harmonious and balanced with a clear vision. Fanatical, tough attitude, the spirit that lights up, encourage them to express their attitude injustice to the public in interpreting the verses of the Qur'an